Consent to Sexual Intercourse by the Non-Disclosure of Material Facts. - Mohamad Yunus, Mohamad Ismail (ROYAL MALAYSIA POLICE, 2015)
For an illustration, if a man who is suffering from venereal disease or even AIDS conceals this fact from his sexual partner, would her consent to the sexual intercourse be vitiated base on mistaken belief as to the nature and quality of the act? An analogy to this situation would be such as the complainant consenting to an immunization shot and, instead, being purposefully injected with cancerous cells. For sure, such consent to the application of force (the injection) has obviously been vitiated by the fraud.